National Health Service Bill : Summary of proposed new service (London : His Majesty's Stationery Office)
1946-03 1946 1940s 19 pages 4 the various cash benefits — including sickness and maternity benefits — for which that Bill provides. A proportion of their contributions will be used to help to finance the health services under the present Bill, but the various health service benefits under the present Bill are not made conditional upon any insurance qualification or the proof of having paid contributions. There are no waiting or qualifying periods. 6. The service is to be available from a date to be declared by Order in Council under the Bill, and it is hoped that this will be at the beginning of the year 1948. The Service to be free of fees or charges 7. The health service is to be financed partly from the exchequer, partly from local rates, partly from the help (mentioned above) which part of the National Insurance contributions will give. There are to be no fees or charges to the patient, with the following exceptions: (i) There will be some charges (to be prescribed later by regulations) for the renewal or repair of spectacles, dentures and other appliances, where this is made necessary through negligence in the care of the articles provided. (ii) There will be charges (taking into account ability to pay) for the provision of domestic help under the Bill and for certain goods or articles (e.g. supplementary foods, blankets, etc.) which may be provided in connection with maternity and child welfare or the special care or after-care of the sick. (iii) It will be open to people if they wish, in certain cases, to pay for additional amenities within the arrangements of the service — e.g. to pay extra for articles or appliances of higher cost than those normally made available, or to pay charges for private rooms in hospitals (which they will nevertheless be able to obtain free where privacy is medically necessary). General organisation of the service 8. The Bill places a general duty upon the Minister of Health to promote a comprehensive health service for the improvement of the physical and mental health of the people of England and Wales, and for the prevention, diagnosis and treatment of illness. To bring physical and mental health closer together in a single service, it transfers to the Minister the present administrative functions of the Board of Control in regard to mental health (the Board retaining only its quasi-judicial functions connected with the liberty of the subject). 9. The Bill proposes that the Minister shall discharge his general responsibility through three main channels:— (a) For parts of the service to be organised on a new national or regional basis — i.e. hospital and specialist services, blood transfusion and bacteriological laboratories for the control of epidemics — the Minister is to assume direct responsibility; but he is to entrust the actual administration of the hospital and specialist services to new regional and local bodies established under the Bill. These bodies are to act on his behalf in suitable areas to be prescribed by him, and they are to include people of practical experience and local knowledge and some with professional qualifications. Special provision is made for hospitals which are the centres of medical and dental teaching. (b) For parts of the service to be organised as a function of local government — i.e. the provision of new Health Centre premises and a variety of local domiciliary and clinic services — direct responsibility is put upon the 292/847/4/115